La littérature d’exil est-elle une littérature mineure ? - Noghrehchi, Hessam (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Can the exile literature, as a literary production of a social minority, become a minor literature? Analyzing the example of the Persian speaker authors who write in French, this article tries to depict the various aspects of the minor literature and the exile literature, for instance: political context which determines the act of writing, collective character of the literatures in question, difficulties related to the choice of language, importance of writer’s and readers’ “doxa”, image that the society imposes on the author. These reflections show a seeming resemblance between the two types of literature just to contrast one with the other and examine the reasons, as well as the consequences, of the differences that can be observed.